A Daily Activity Book as a Strategy of Learning English for Esp Learners to Improve Writing Skill - Linta Wafdan Hidayah; Rahmawati Ardila (Universitas Islam Madura, 2019)
Teaching English for ESP Learners needs more strategies to improve their skill in English. Writing skill as one of skill in English, sometimes the students lack the confidence to pour their ideas into paper streaks. It needs a fun method for ESP Learners, so they are more interested in learning English that they have been consider difficult and boring. There are many steps to writing text, that is, when students have unwritten ideas and want to convey them in written text in the form of ideas and opinions, it is advisable to start sentences with simple patterns by describing stories and essays. No needed to think about Spelling, vocabulary, grammar, and organization, because all of these points will flow by themselves along with the expertise and fluency and proficiency of students in writing. Here, the researcher uses writing daily activity book to improve young learner’s writing skill. The researcher believes that this technique can help young learner to explore their writing skill to explore their idea and feelings in daily story.Moreover, in daily activity book the students can give the picture as they want. This strategy is considered be effective and funnier because indirectly ESP Learners can learn to write better. ESP learners can find out how to write the right techniques. The researcher uses qualitative experimental research for ESP learners, especially for accounting economic students of UIM Pamekasan, to conduct this research. From the finding discussion have result the score of the standard deviation for the experimental group is 5,140 and 6,703 is the standard deviation for the control group. Here, can be sum up that use a daily activity book can improve the students’ writing skill. Keywords: Daily activity book, ESP learners, writing skill Abstrak: Mengajar Bahasa Inggris untuk peserta didik ESP membutuhkan lebih banyak strategi dalam meningkatkan keterampilan mereka berbahasa Inggris. Keterampilan menulis sebagai salah satu keterampilan dalam bahasa Inggris, yang terkadang siswa kurang percaya diri untuk menuangkan ide-ide mereka ke dalam coretan kertas. Dibutuhkan metode yang menyenangkan untuk Peserta didik ESP, sehingga mereka lebih tertarik untuk belajar bahasa Inggris yang mereka anggap sulit dan membosankan. Ada beberapa langkah menulis teks, yaitu, ketika siswa memiliki ide-ide tidak tertulis dan ingin menyampaikannya dalam teks tertulis yang berbentuk ide dan pendapat, disarankan untuk memulai kalimat dengan pola sederhana dengan menjelaskan cerita dan esai. Tidak perlu memikirkan Ejaan, kosakata, tata bahasa, dan organisasi, karena semua poin ini akan mengalir dengan sendirinya bersama dengan keahlian dan kelancaran serta kemahiran siswa dalam menulis. Di sini, peneliti menggunakan menulis buku aktivitas harian untuk meningkatkan keterampilan menulis peserta didik ESP. Peneliti percaya bahwa teknik ini dapat membantu peserta didik ESP dalam menningkatkan keterampilan menulisnya untuk mengeksplorasi ide dan perasaan mereka dalam cerita sehari-hari. Terlebih lagi, dalam buku kegiatan sehari-hari siswa dapat memberikan gambar sesuai keinginan mereka. Strategi ini dianggap efektif dan menarik karena secara tidak langsung peserta didik ESP dapat belajar menulis lebih baik dengan teknik yang benar. Peneliti menggunakan penelitian eksperimental kualitatif untuk peserta didik ESP, dengan subjek penelitian adalah mahasiswa ekonomi akuntansi UIM Pamekasan. Dari pembahasan temuan menghasilkan skor standar deviasi untuk kelompok eksperimen adalah 5.140 dan 6.703 adalah standar deviasi untuk kelompok kontrol. Di sini, dapat disimpulkan bahwa menggunakan strategi buku aktivitas harian dapat meningkatkan keterampilan menulis siswa.